Role of Compatibilizer in Improving the Properties of PLA/PA12 Blends - Raj, Amulya; Samuel, Cedric; Prashantha, Kalappa (Frontiers in Materials, 2020)
Engineering properties of partially-biobased poly(L-Lactide)/poly(amide-12) (PLA/PA12) blends are here addressed using a functional compatibilizer, namely poly(L-Lactide) grafted maleic anhydride (PLA-g-MA). PLA/PA12 blends with compatibilizers are processed using twin-screw extrusion and the amount of PLA-g-PMA is here optimized with respect to final blend properties such as ductility, impact toughness, and thermal resistance. Blend morphologies depict the enhanced PA12 dispersion into PLA-g-MA with strong interfacial adhesion, in accordance with a compatibilization effect of PLA-g-MA in PLA/PA12 blends. Ductility of the compatibilized blends shows remarkable improvements with the highest ductility which is close to 290% for an optimized PLA/PA12/PLA-g-MA weight composition (respectively 69/30/1). The impact strength of compatibilized blends showed a similar two-fold improvement for compatibilized blends. Morphology of injection molded samples revealed finer dispersion and stronger interfaces. The morphology of the transversal section displayed fibrillation of PA12 for PLA-g-MA content up to 2 wt.%. Fibrillation and lower droplet size seemed to play a key role in the improvement of ductility in compatibilized blends. Considerable synergy was detected in the dynamic mechanic analysis of the compatibilized blends. The thermal resistance of the PLA/PA12 blends showed improvement and this behavior could be due to the formation of copolymer leading to additional interfacial crystallization. This study consequently indicates that PLA-g-MA is an efficient compatibilizer for partially-biobased PLA/PA12 blends with potential applications into the automotive and electronic industry.